2008
DOI: 10.1510/icvts.2007.165027
|View full text |Cite
|
Sign up to set email alerts
|

Endovascular treatment of chronic type A dissection

Abstract: Type A aortic dissection is usually treated with standard surgery, requiring cardiopulmonary bypass and sometimes deep hypothermia. Besides the well-established procedure, mortality and complications are considerable. Using the knowledge and lessons learned from the endovascular treatment of descending aortic diseases, emerging reports describe new approaches to the condition, using endovascular stent-grafts. This report describes an endovascular treatment of a chronic type A aortic dissection without cardiopu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 6 publications
0
8
0
1
Order By: Relevance
“…Furthermore, almost all the reports of successful endovascular treatment of TAAD employed the closest coronary artery as the landmark during the procedure. [6][7][8][9][10]17,18 We used major and minor anatomical criteria to define morphological suitability and difficulty for endovascular repair. Because there is no commercially available fenestrated or branched endograft currently that permits flow into the coronary arteries, we selected 20 mm as the minimum proximal length sufficient for the stent to seal the proximal entry tear.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, almost all the reports of successful endovascular treatment of TAAD employed the closest coronary artery as the landmark during the procedure. [6][7][8][9][10]17,18 We used major and minor anatomical criteria to define morphological suitability and difficulty for endovascular repair. Because there is no commercially available fenestrated or branched endograft currently that permits flow into the coronary arteries, we selected 20 mm as the minimum proximal length sufficient for the stent to seal the proximal entry tear.…”
Section: Discussionmentioning
confidence: 99%
“…Current endovascular treatment of TAAD, as with TBAD, involves sealing the proximal entry tear and remodeling the dissected aorta. [6][7][8][9][10] A detailed description of ascending aortic morphology in patients with TAAD should be presented before this treatment is standardized.…”
mentioning
confidence: 99%
“…Long-term outcome data for aTEVAR are lacking due to small number of cases. Reported periprocedural complications with aTEVAR include endoleaks, stent buckling [14], stent migration [15], delivery device retention [9], and stroke. Further, the optimal degree of oversizing has not been delineated, although excess oversizing has been associated with aortic insufficiency.…”
Section: Endovascular Repairmentioning
confidence: 99%
“…Since then, aortic surgery has developed quickly because of advances in cardiopulmonary bypass, postoperative care, and surgical techniques that reduce the mortality rates of these procedures 4,5. At present, less invasive techniques, such as endovascular interventions, are performed, especially in thoracic and thoracoabdominal aortic disease, depending on factors such as whether the patients would be at high risk during conventional procedures 6,7. Recent studies and case reports have shown the possibility of performing endovascular procedures in the ascending aorta, which seems to be a promising approach 7…”
Section: Introductionmentioning
confidence: 99%
“…These issues are relevant in the context of congenital diseases such as Marfańs syndrome,7 Ehlers-Danlos syndrome,8 congenital aortic valve malformations, and acquired aortic valve diseases 9…”
Section: Introductionmentioning
confidence: 99%